Resiko Umur Dan Paritas Ibu Hamil Pada Kejadian Preeklampsi Eklampsi - Rahmawati, Rahmawati; Fauziah, Fauziah (Bunda Edu-Midwifery Journal (BEMJ), 2019)
Background: East Kalimantan Provincial Health Office noted that during 2015 there was an increase in maternal mortality and childbirth. Because most deaths caused by bleeding as many as 33 cases, hypertension in pregnancy as many as 31 cases. RSUD AW SjahranieSamarinda, reported that theincidence rate of eclampsipreeklampsi increased from 2014 that is 1.09% to 1.59% in 2015. Objective: The objective of the research is The purpose of this study was to determine the relationship between maternal age and parity risk factors in the occurrence of eclampsipreeclampsi in RSUD AW Sjahranie.Methods: : Observational analytical research with case control approach. Research location in RSUD AW Sjahranie. Sampling by purposive sampling which is limited by inclusion and exclusion criteria. The analysis test by calculating Chi squared to know the existence of relation of pregnant mother and parity with pre eclamptic event eclampsi then calculate odds ratio to know the big of risk factor with 95% confidence interval and error rate 5%.Results: Obtain Chi square calculate age risk factor equal to 9.82 bigger compared with Chi squared table at degrees of freedom 1 with 5% error level is 3,841 then Chi squares count lebih dari Chi squared table, thus Ho rejected and Ha accepted. Chi square count parity lebih dari chi squared table 18,243 lebih dari 3,841 means Ho refused and Ha accepted. Odds age ratio at risk of 3.596 is greater than the age that is not at risk. Odds ratios Parity 1 and lebih dari 3 have a risk of eclampsiapreeclamption of 5.26 times greater than non-risk parity (Parity 2 - 3).Suggestion: health workers to increase the number and quality of midwifery services, especially in giving counseling and counseling especially in pregnant women with age at risk of eclampsiapreeclamption (ageless than 20 years and over 35 years) or screening pregnant mother so that can be anticipated immediately if Found signs of pre-eclampsi exclusion in pregnant women. For institutions to continuously improve the provision of information on the eclampsiapreeclamption to students.